Synthesis and NH3 gas sensing characteristics of rGO/WO3 nanocomposite - Do, Quang Dat; Nguyen, Duc Hoa; Chu, Thi Quy; Lam, Van Nang; Chu, Manh Hung; Nguyen, Van Hieu (Old Journal, 2018)
Synthesis of advanced functional nanomaterials for gas sensor application has been the topic of interested in recent years. Herein, the rGO/WO3 nanocomposite was synthesized by facile and scalable hydrothermal method at temperature of 120°C for gas sensor applications. Materials were characterized by some advanced techniques such as scanning electron microscopy (SEM), and UV-vis spectroscopy. Results reveal that the rGO/WO3 nanocomposite was obtained in which WO3 nanowires of an average diameter of less than 10 nm with a length up to 300 nm. UV-vis measurement reveals the semiconductor property of WO3 with a wide band gap of about 2.9 eV. Gas sensing measurements demonstrate that the rGO/WO3 nanocomposite can monitor low level concentration of highly toxic NH3 gas down to 25 ppm.